Da'wah Communication in Enhancing Islamic Understanding among Students at IAIN Ternate in the Digital Era - Ulwia Usman; Makbul A.H. Din (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
The development of the digital sphere has brought significant changes in communication methods and the dissemination of information in various aspects, especially in the field of da'wah. This study aims to explain the influence of digital technology in increasing the Islamic understanding of students at IAIN Ternate, North Maluku. The research utilizes a qualitative approach with a literature review method. Primary data sources were obtained from various da'wah content on social media, such as content from Ustadz Abdus Somad, while secondary data was gathered from books, articles, and other references relevant to the research. Data analysis was conducted using content analysis techniques, utilizing Everett Rogers' Diffusion of Innovation theory. The results of this research show that the use of digital technology in da'wah can increase the creativity of preachers and serves as an effective medium for conveying da'wah messages, enabling those messages to be easily received by the audience—in this context, the students of IAIN Ternate